Impact of a national immunisation program on herpes zoster incidence in Australia. Issue 4 (April 2022) - Lin, Jialing; Dobbins, Timothy; Wood, James G.; Bernardo, Carla; Stocks, Nigel P.; Liu, Bette
Highlights: We evaluated the impact of a zoster vaccination program on zoster incidence. Within two years zoster incidence fell by 2.25/1000 per year in 70–79 year-olds. In 2 years, we estimated 7000 zoster cases were prevented through the program. Summary: Objectives: To evaluate the impact of the National Herpes Zoster (zoster) Immunisation Program in Australia on zoster incidence. Methods: Ecological analysis of zoster incidence related to timing of implementation of the national program in vaccine-targeted (70–79 years) and non-targeted age groups (60–69 and 80–89 years) during January 2013–December 2018 was estimated using interrupted time-series analyses. Results: Prior to program commencement (Jan 2013–Oct 2016) in patients aged 60–69, 70–79 and 80–89 years, incidence was mostly stable averaging respectively 7.2, 9.6 and 10.8 per 1000 person-years. In the two years following program commencement, incidence fell steadily in those aged 70–79 years, with an estimated decrease of 2.25 (95% CI: 1.34, 3.17) per 1000 person-years per year, with women having a greater decrease than men (2.83 versus 1.68, p-interaction<0.01). In the two non-vaccine-program-targeted groups there was no evidence of reduction in zoster incidence: 60–69 years, 0.46 (95% CI: -0.46, 1.38) and 80–89 years, 0.11 (95% CI: -1.64, 1.87). Conclusions: Two years after implementation, an estimated 7000 zoster cases were prevented through the national program. With known waning vaccine efficacy, continued surveillance is needed to ensure these early reductions in incidence are sustained.